War veterans as peace builders - Kostić Novica (Temida)
In the period from 1991. to 1999. over 1500000 people in former Yugoslavia were members of dozens military formations that participated in the war in different manners and with various motives. These persons have actively contributed to the tragedy caused by war, that was and for some time will be the most important factor of social and personal relationships between individuals and the nations in the member states of former Yugoslavia. They are now left on their own and exposed to manipulation by nationalist centers and certain politicians. Because of their wartime past, they are usually depicted as the carriers of nationalistic and warmongering ideas on the 'other' side. However, viewed from the aspect of peace-building, ex-soldiers represent a significant potential, because many of them, in fact, have a need to contribute to building a more just society and feel responsible for what happened. In this paper it is discussed how some war veterans decided to join forces and contribute to the reconciliation in the former Yugoslavia by their joint activities.